Akibat Hukum Pemilik Tidak Mengambil Pesanan Jahitan di Desa Hamparan Perak Kecamatan Hamparan Perak Kabupaten Deli Serdang Perspektif Fatwa DSN-MUI No: 112/DSN MUI/IX/2017 Tentang Akad Ijarah - Fazira, Aina; Sahlia, Sahlia (UNES Law Review, 2023)
One of the professions of residents in Hamparan Perak Village is as a tailor. The problem often faced by tailors in Hamparan Village is that consumers do not take orders. The aim of this research is to determine the factors causing not taking orders for stitches and the impact and legal consequences of not taking orders for stitches from the perspective of DSN-MUI Fatwa NO: 112/DSN-MUI/IX/2017 Concerning Ijarah Contracts. This type of research is empirical juridical with a living case studies approach and a conceptual approach. Data was collected using interviews and document study methods, then the data was processed and analyzed using qualitative methods. The results of the research showed that stitches were not taken because the orderer did not have the money when the time came for the order to be taken, therefore the tailor suffered material and material losses, namely energy and costs to buy additional materials to adjust the order. Based on the DSN-MUI Fatwa NO: 112/DSN-MUI/IX/2017 concerning the Ijarah Agreement, the legal consequences of not taking the order by the customer, means that the tailor in this case has the right to sell the order to a limited extent and only take it as sewing wages as agreed at the beginning and additional maintenance costs are added so that the stitching matches what the customer ordered while it is in the hands of the tailor.